2016
DOI: 10.23910/ijbsm/2016.7.5.1531a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Herbicides on Weed Dynamics, Growth and Yield of Chrysanthemum (Dendranthema grandiflora T.)

Abstract: A field experiment was conducted at Floricultural Research Station, Hyderabad, Telangana under irrigated conditions for three consecutive years from 2009−10 to 2011−12 on Chrysanthemum variety Mayuri with pre-emergence herbicides Butachlor, Pendimethalin, Fluchloralin and Diuron in different concentrations. The experiment was laid out in randomized block design with three replications and ten treatments in a set. The dominating weed species observed in the experimental site were Parthenium histerophorus, Amara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…2). The results are in accordance with the findings of Kameswari et al [8] reported greater nutrient availability in different media in which the combination of cocopeat + sand + FYM + vermicompost recorded the greatest height of the plant in Dendranthema grandiflora. The combined application of cocopeat and vermicompost has micropores.…”
Section: Vegetative Parameterssupporting
confidence: 92%
“…2). The results are in accordance with the findings of Kameswari et al [8] reported greater nutrient availability in different media in which the combination of cocopeat + sand + FYM + vermicompost recorded the greatest height of the plant in Dendranthema grandiflora. The combined application of cocopeat and vermicompost has micropores.…”
Section: Vegetative Parameterssupporting
confidence: 92%
“…There is evidence for growing chrysanthemum plants in soilless growing media, including perlite, peat, creamsite, rice husk ash 4 , soilrite 5 , treated coir dust 6 , carbonized rice husk 7 and cocopeat + soilrite, cocopeat + compost 8 . The plant height, spread, flower weight and number of flowers in chrysanthemum variety 'Punjab Anuradha' were observed to be maximum in cocopeat + sand + FYM + vermicompost in equal ratio 9 . The cocopeat-based medium combination could replace the traditional potting medium (soil) for pot production in chrysanthemum cv.…”
mentioning
confidence: 94%
“…An increase in the number of leaves per plant may also be due to adequate availability of nitrogen, boron, potassium and zinc content in media [36]. The growing media that are light in weight, rich in nutrients and well-drained are considered best for the growth and development of flowering plants [17,[52][53][54][55].…”
Section: Vegetative Parametersmentioning
confidence: 99%